Using Social Theory in Higher Education - Y.S. Low, Remy; Egan, Suzanne; Bell, Amani (Springer Nature, 2024)
This open access book offers a unique and refreshing view on working with social theory in higher education. Using engaging first-person accounts coupled with critical intellectual analysis, the authors demonstrate how theory is grappled with as part of an ongoing practice rather than a momentary disembodied encounter. In a structure that creates a space for relational dialogue, each chapter is followed by a response from another author, demonstrating the varied interpretive possibilities of social theory. Collectively the authors invite the reader to engage with them in questioning the usefulness of social theory in higher education teaching and research, in considering its possibilities and limits, and in experiencing the opportunity it offers to understand ourselves and our work differently. Written in a way that is scholarly yet accessible, the contributors explore how social theories can be used to think through issues that are emerging as key social and political concerns in higher education and beyond. The book will be of interest to advanced undergraduates, postgraduates, and early-career academics, as well as established scholars.